Penta Helix Model Approach Strategy Towards the Effectiveness of Stunting Reduction Programs in Surabaya City - Utomo, Priyo; Adhitya Pratama, Devangga Putra (IJEBD (International Journal of Entrepreneurship and Business Development), 2024)
Purpose: This study examines the effectiveness of the Penta Helix model—integrating academia, business, community, government, and media—in reducing stunting rates in Surabaya, Indonesia. Through path analysis, the research assesses the individual and collective impacts of these sectors on the effectiveness of the stunting reduction program. The findings reveal that government, business, and media sectors play significant roles in the success of the program, with government involvement being the most critical factor. In contrast, academia and community involvement demonstrate limited impact, suggesting potential gaps in research application and community engagement. Design/methodology/approach: This study employs a quantitative research design to examine the effectiveness of the Penta Helix model in reducing stunting rates in Surabaya. The research uses Structural Equation Modeling (SEM) with Smart PLS 3 to analyze the relationships between various variables within the model. A total of 250 respondents were selected for the study. The sample size was determined based on the recommendations for SEM, which suggest a minimum of 200 respondents for robust analysis. Findings: The study’s results are contextualized within Indonesia’s national policies, particularly the National Strategy to Accelerate Stunting Prevention (Stranas Stunting), highlighting the importance of governmental support and coordinated efforts across sectors. The positive contributions of the business sector underscore the value of public-private partnerships, while the significant role of media reinforces the importance of strategic communication in public health initiatives. Research limitations/implicationsThe need for stronger linkages between academic research and practical implementation, as well as more robust community engagement strategies. These insights have important implications for refining the Penta Helix model to achieve more effective and sustainable stunting reduction outcomes in Surabaya and other regions. By addressing these gaps, the model can be optimized to better support Indonesia’s ongoing efforts to combat stunting, ultimately contributing to improved public health outcomes nationwide. Practical implications: Given that a majority of the sectors (Government, Business, and Media) show significant individual contributions, it is reasonable to conclude that the hypothesis that all variables collectively have a significant effect on the effectiveness of the stunting reduction program is likely accepted. However, this conclusion is based on the assumption that the combined effect of the variables is assessed through an appropriate overall model fit measure, which is typically significant if most individual paths are significant. Originality/value: This research represents an original contribution to the field of public health and urban development through its innovative application of the Penta Helix model to the issue of stunting reduction in Surabaya. While existing studies have explored various approaches to addressing stunting, this study distinguishes itself by integrating a Penta Helix framework a multi-stakeholder model involving academia, business, government, community, and media into the analysis of program effectiveness.